2018
DOI: 10.1002/hfm.20766
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the influences of resilience engineering on health, safety, and environment and ergonomics management system by using Z‐number cognitive map

Abstract: This study evaluates and analyzes the impacts of resilience engineering (RE) principles on integrated health, safety, environment, and ergonomics (HSEE) management system. In decision sciences, information should be reliable due to uncertainty and vagueness existing in information. To this end, in this study, the concept of Z‐numbers with fuzzy cognitive map (FCM) approach is integrated and a novel approach named Z‐number cognitive map is proposed. The main advantages of the proposed approach are determination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…The results showed that senior management commitment (0.827) had the highest effect on the environment, learning (0.792) had the highest effect on health, readiness (0.786) had the highest effect on ergonomics, and awareness (0.776) had the highest effect on safety. 42…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that senior management commitment (0.827) had the highest effect on the environment, learning (0.792) had the highest effect on health, readiness (0.786) had the highest effect on ergonomics, and awareness (0.776) had the highest effect on safety. 42…”
Section: Discussionmentioning
confidence: 99%
“…[54] "a paradigm for safety management that concentrates on how to help people deal with complexity under stress to achieve success" (p. 336) [56] "an organizational culture that fosters safe practices for improved safety in an ultra-safe organization striving for cost-effective safety management" (p. 297) [58] "capability to sustain or rapidly return to a steady state that allows the organization to continue operation during or after a major event or in the presence of continuous stresses" (p. 191) [59] "ability of an organization to regulate its function before, during, and after perturbations and fluctuations, so that it can continue the operations required under both predicted and unpredicted situations" (p. 142)…”
Section: Authorsmentioning
confidence: 99%
“…Instruments 2 [29] and 15 [57] measured characteristics that were different to those suggested by Wreathall in [27] or [19], while instrument 9 [51] was the only one to explicitly measure the four capabilities of a resilient organisation [19]. The instruments developed by teams led by Shirali and Azadeh appear to be central, illustrated in studies 6, 7, 10, 11, 14 and 16 [48,49,52,53,56,59]. Two instruments measured Resilience Safety Culture (RSC) [56,57], while one measured Resilience Safety Climate [55].…”
Section: Authorsmentioning
confidence: 99%
See 1 more Smart Citation
“…e concepts of Z-valuation [3], Z + -number [4] and Zinformation [5] are closely related to the concept of Znumbers. e proposed four concepts are shown in Table 1, where u A is the membership function of A and p X is the probability distribution of X. e second aspect is languagetype Z-number calculation and related extension [6,7], for example, Zarrin and Azadeh [8] combined Z-number with fuzzy cognitive map (FCM) and proposed a novel approach named Z-number cognitive map. ey evaluated and analyzed the impacts of resilience engineering (RE) principles on integrated health, safety, environment, and ergonomics (HSEE) management system.…”
Section: Introductionmentioning
confidence: 99%